Designing a Salary Structure for SME XYZ in the Bogor Regency Using a Regression-Based Approach Based on Job Value - Moreno Verli Widjanarko; Fahrur Rozi Harahap; Vanessa Azzahra Latief; Imantaka Brillianda; Lindawati Kartika (Jurnal Ilmiah Wahana Pendidikan, 2023)
Small and Medium Enterprises (SMEs) play a crucial role in contributing to the economy, with the potential to sustain and drive national economic growth. Among the various industries within the SME sector, the culinary sector is often chosen by SME entrepreneurs. Within SMEs, human resources hold significant importance. The effectiveness of employees in fulfilling their responsibilities within the organization is vital for ensuring smooth business operations. Establishing a robust compensation system is of utmost importance for Indonesian SMEs. A well-designed, adequate, and equitable compensation system is necessary to appropriately recognize employees' contributions to the organization. This research aims to identify the existing compensation system, analyze the underlying factors influencing payroll decisions, and evaluate the ideal salary system for implementation. Primary and secondary data sources are utilized in this research. A nonprobability sampling method, specifically census sampling, is employed. The point system method and simple linear regression analysis are utilized to analyze the data. The factors influencing salary determination at SME XYZ are ranked in order of significance as follows: Responsibility for Records and Reports, Job Complexity, Decision Making, Customer Service Orientation, Responsibility for Equipment, Communication, Initiative, Working Conditions, Experience, and Education. The recommended payroll structure for implementation at SME XYZ is the non-classification payroll structure. This structure offers benefits such as simplified job clustering and improved accuracy in employee career development.